Adsorption of phenol on kenaf‐derived biochar: studies on physicochemical and adsorption characteristics and mechanism - Cho, Eun Ji; Lee, Chang Gu; Jin-Kyu-Kang; Park, Seong Jik (Biomass Conversion and Biorefinery, 2024)
Biochar derived from kenaf, a fast-growing plant, was used as a adsorbent in this study to remove phenol from aqueous solutions. Kenaf-derived biochar (KDB) was prepared at various temperatures (300–750 °C) and the relationship between the phenol adsorption mechanism and physicochemical properties was investigated. The highest phenol adsorption by KDB was achieved at 750 °C, and KDB pyrolyzed at 750 °C (KDB-750) had the lowest O/C (0.11) and H/C (0.01) values as well as the highest specific surface area (116.74 m2/g). Phenol molecules could be adsorbed on the surface of KDB via hydrophobic attraction and π–π interaction. Kinetic studies revealed that the adsorption reached equilibrium at 48 h, and the adsorption process was well explained by the pseudo-second-order model. The maximum phenol adsorbed obtained from equilibrium adsorption experiments was 41.1 mg/g, which is comparable to that reported in the literature. The enthalpy and entropy changes during phenol adsorption by KDB-750 were 22.3 kJ/mol and 64.2 J/K‧mol, respectively. The amount of phenol adsorbed decreased gradually from 38.5 to 32.4 mg/g as the pH of the solution increased from 3 to 9, and it decreased sharply from 32.4 to 28.9 mg/g as the pH increased from 9 to 11. When 0 to 200 mM NaCl was added to the phenol solution, the adsorbed amount decreased from 38.1 to 29.5 mg/g. Moreover, for a KDB-750 dosage of 10 g/L, > 90% of the phenol was removed. Thus, KDB-750, which is a low-cost and abundant adsorbent, could potentially be used as an adsorbent to remove phenol effectively.
Keywords: Adsorption characteristic; Adsorption mechanism; Adsorption of phenol; Biochar; Characteristics and mechanisms; Kenaf; Phenol adsorption; Phenols removal; Physicochemical characteristics; Physicochemical property; Adsorption mechanism; Biochar; Kenaf; Phenol removal; Physicochemical properties